Two new species of Pavonia (Malvoideae, Malvaceae) from southern Bahia, Brazil - Gonçalez, Victor M.; Pfeil, Bernard E.; Antonelli, Alexandre; Duarte, Marília C. (Phytotaxa, 2017)
Two new species of Pavonia subgenus Goetheoides are described (Pavonia gerleniae and Pavonia macrobracteolata) from the wet coastal forests of eastern Brazil. This increases the number of species in the subgenus to 30, which is considered a high level of diversity for arborescent species in this geographically and ecologically limited area. We present morphological descriptions and comments, taxonomic relationships, pictures and conservation status of these species.